Genetic polymorphisms of antioxidant and antiglycation enzymes and diabetic complications: how much can we learn from the genes? - Oikonomou, Dimitrios; Gröner, Jan; Cheko, Ruan; Kender, Zoltán; Kihm, Lars Philipp; Fleming, Thomas; Kopf, Stefan; Nawroth, Peter Paul (Experimental and clinical endocrinology & diabetes, 2018)
There is growing evidence that reactive metabolites, such as reactive oxygen species and dicarbonyls contribute to diabetic complications. Formation, accumulation, and detoxification of these metabolites are controlled by several enzymes, some of which have genetically determined levels of expression or function. This review not only gives an overview of the different SNPs studied in patients with diabetes mellitus type 1 and type 2, but in addition attempts to bridge the gap between a genetic study and clinical use. Therefore, not only the results of the studies are reviewed, but also their use in identification of subgroups where an increased or decreased risk for a diabetic complication is described, as well as their use in developing novel therapeutic options based on understanding the contribution of an enzyme to a given complication.